Etnis dan Pilihan Politik dalam Pilkada Dumai Tahun 2005 - ADLIN, ADLIN (Politeia: Jurnal Ilmu Politik, 2013)
General election of regional head (Pemilukada) is influenced by various factors. This study explains the influence of ethnics towards political choice in local election. This study is using political behavior approach. Collecting data of this study is using field research and data anal-ysis using quantitative and qualitative method. The finding is, influence of ethnics found in sev-eral voter especially in case Malay Riau ethnics. But, in other case, several voters from Java ethnic and another âvisitorsâ ethnics vote without identification of ethnic. It can be seen from the factors that influence voter for voting Zulkifli AS-dr Sunaryo candidate. In the local election of Dumai in 2005 found mostly voters who votes Zulkifli AS-Dr Sunaryo candidate did not vote because of ethnicsâ identification. So, in this case there is correlation between ethnics and polit-ical. But the relation is imperfect. In other words there are many another relations except eth-nicsâ factors that is linked with political choice in local election of Dumai City in 2005.Keywords: Voter behavior, local election, etnicity.